Air quality impacts from oil and natural gas development in Colorado - Detlev Helmig (Elementa: Science of the Anthropocene, 2020)
The rise of hydraulic fracturing techniques has fostered rapid growth of oil and natural gas (O&NG) extraction in areas across the United States. In the Denver-Julesburg Basin (DJB), which mostly overlaps with Weld County in the Northern Colorado Front Range (NCFR) north of the City of Denver Metropolitan Area (DMA), the well drilling has increasingly approached, and in many instances moved into urban residential areas. During the same time, the region has also experienced steady population growth. The DMA – NCFR has been in exceedance of the ozone U.S. National Ambient Air Quality Standard (NAAQS) and was designated a non-attainment area of the standard in 2007. Despite State efforts to curb precursors, ozone has consistently remained above the standard. A growing number of atmospheric studies has provided an ever increasing body of literature for assessing influences from O&NG industry emissions on air quality in the DMA-NCFR. This paper provides 1. An overview of available literature on O&NG influences on the regional air quality, 2. A summary of the pertinent findings presented in these works, 3. An assessment of the most important pollutants and air quality impacts, 4. Identification of knowledge and monitoring gaps, and 5. Recommendations for future research and policy.